Addressing the impacts of climate change in the Philippine agriculture sector - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
The National Economic and Development Authority (NEDA) is responsible for advising the Philippine President on national development planning, including recommending the level of the annual government expenditure as stipulated in the 2011-2016 Philippine Development Plan and Public Investment Program. In NEDA, the Agriculture, Natural Resources and Environment Staff (ANRES) pro-vides technical support in coordinating the formulation of national plans and policies for agriculture, natural resources and agrarian re-form sectors. The NEDA-ANRES has expressed strong interest to develop and apply new methods to evaluate current policies and formulate future policies, particularly for the agriculture sector.